A quaternary complex microalloyed steel material and a method for producing the same
Patent Information
- Application Number
- CN202611436656.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-16
- Publication Date
- 2026-10-30
AI Technical Summary
[0009]本发明的目的在于提供一种四元复合微合金化钢材及其生产方法,通过低碳-低钼-多元复合微合金化的成分设计和优化的TMCP工艺,解决现有耐火钢合金成本高、屈强比偏高、高温强度稳定性不足的技术问题
[0056](1)显著降低合金成本:本发明将Mo含量控制在0.10%~0.25%,较传统耐火钢(Mo≥0.40%)降低40%~75%,同时通过Nb-V-Ti多元复合微合金化补偿高温强度,吨钢合金成本降低15%~25%。
Smart Images

Figure CN123005243A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of steel material manufacturing, and more specifically, to a quaternary composite microalloyed steel and its production method. Background Technology
[0002] With the development of modern architecture towards high-rise and large-span structures, the fire safety of steel structure buildings has received increasing attention. The strength and stiffness of ordinary structural steel decrease sharply under high-temperature environments (such as fire conditions). When the temperature reaches 600℃, its yield strength is usually only about 1 / 3 of the yield strength at room temperature, which is difficult to meet the fire safety requirements of building structures.
[0003] Traditional fire-resistant steels are typically designed with a high Mo (mass fraction ≥ 0.40%) content, utilizing Mo's solid solution strengthening and high-temperature stability to ensure the steel's high-temperature strength. For example, the Mo content in early Japanese fire-resistant steels such as NSFR400 and NSFR490 generally exceeded 0.5%. However, Mo is a precious metal element and expensive; a high Mo content significantly increases the production cost of fire-resistant steel, limiting its widespread application to some extent. Furthermore, excessively high Mo content can also deteriorate the steel's weldability and low-temperature toughness.
[0004] The existing low-Mo steel has the following problems: (1) The precipitation strengthening effect of a single microalloying element is limited, and the high-temperature strength stability is insufficient; (2) The volume fraction and morphology of bainite are not properly controlled, resulting in a high yield strength ratio (>0.85) and insufficient seismic performance; (3) There is a lack of precise control over the size, distribution and high-temperature evolution of nanoscale precipitates.
[0005] In addition, most existing refractory steel patents use a single bainitic structure or a ferrite-pearlite structure, which has the problem of a high yield strength ratio or insufficient high-temperature strength.
[0006] Chinese patent CN101171354B discloses a refractory steel with a composition of C: 0.01%~0.03%, Mo: less than 0.8%, Nb: 0.01%~0.30%, and Ti: 0.005%~0.03%. However, its upper limit of Mo content is relatively high, and there is still room for reducing the alloy cost.
[0007] Chinese patent CN103667963B discloses a low-carbon bainitic building steel with a yield strength ratio <0.8, designed with a composition of C: 0.030%~0.10%, Mo: 0.15%~0.40%, Nb: 0.055%~0.15%, and V: 0.02%~0.08%. However, its Nb content is relatively high (≥0.055%), resulting in higher alloy costs. In addition, its bainite content is too high, and the microstructure stability at high temperatures needs to be verified.
[0008] Therefore, there is an urgent need to develop a fire-resistant building steel with low alloy cost, low yield strength ratio, excellent fire resistance, and simple production method. Summary of the Invention
[0009] The purpose of this invention is to provide a quaternary composite microalloyed steel and its production method. Through the composition design of low carbon-low molybdenum-multi-element composite microalloying and the optimized TMCP process, the technical problems of high cost, high yield strength ratio and insufficient high temperature strength stability of existing refractory steel alloys are solved.
[0010] The embodiments of the present invention are achieved through the following technical solutions:
[0011] A quaternary composite microalloyed steel, with a chemical composition by weight percentage including: C: 0.05%~0.12%, Si: 0.15%~0.45%, Mn: 1.20%~1.80%, Mo: 0.10%~0.25%, Nb: 0.020%~0.060%, V: 0.030%~0.080%, Ti: 0.008%~0.025%, Cr: 0.20%~0.50%, Ni: 0.10%~0.30%, Cu: 0.15%~0.35%, Als: 0.015%~0.050%, N: 0.006%~0.015%, with the balance being Fe and unavoidable impurities;
[0012] Unavoidable impurities include P and S, with P ≤ 0.020% and S ≤ 0.010%.
[0013] Preferably, the microstructure of the steel includes ferrite and bainite, with the ferrite volume fraction being 45%~55% and the bainite volume fraction being 45%~60%.
[0014] Preferably, the bainite is lath bainite, and the size of the bainite lath bundles is ≤15μm.
[0015] Preferably, the steel contains nanoscale MC-type composite carbide precipitates, the main types of which include (Nb,V,Mo)(C,N) and (Ti,Mo)(C,N), and the size distribution range of the nanoscale MC-type composite carbide is 3nm~18nm.
[0016] Preferably, the mass fraction of the nanoscale MC-type composite carbide in the rough rolling state is 0.015%~0.045%, and the mass fraction after high-temperature tempering is 0.040%~0.090%, wherein the nanoscale MC-type composite carbide with a size of less than 10nm accounts for no less than 55% of the total mass fraction of the MC-type composite carbide.
[0017] Preferably, the small-angle grain boundary density of the steel is ≥3.5mm / mm².
[0018] Preferably, the steel has a yield strength at room temperature ≥460MPa, a tensile strength ≥600MPa, an elongation after fracture A ≥20%, and a yield strength ratio ≤0.80;
[0019] The yield strength under high-temperature tensile conditions of 600℃×3h is not less than 2 / 3 of the yield strength at room temperature.
[0020] The roles and design basis of each alloying element in this invention are as follows:
[0021] Carbon (C): C is the most fundamental element ensuring the strength of steel, enhancing strength through solid solution strengthening and carbide formation. Too low a C content (<0.05%) makes it difficult to guarantee room temperature strength and bainitic hardenability; too high a C content (>0.12%) worsens weldability and low-temperature toughness, and promotes the formation of coarse cementite (M3C) at high temperatures, reducing refractory properties. This invention controls the C content to 0.05%~0.12%, preferably 0.06%~0.10%, ensuring both strength and weldability / refractory properties.
[0022] Silicon (Si): Si is a strong deoxidizing element with strong solid solution strengthening properties, which can improve the room temperature and high temperature strength of steel. If the Si content is too low, deoxidation is insufficient, and the solid solution strengthening effect is inadequate; if the Si content is too high (>0.45%), it promotes surface oxidation and decarburization of the steel, deteriorating surface quality and reducing the steel's plasticity and weldability. This invention controls the Si content to be 0.15%~0.45%, preferably 0.20%~0.35%.
[0023] Manganese (Mn): Mn is a key element for improving hardenability and strength. It can expand the austenite region, lower the phase transformation temperature, and promote bainite formation. If the Mn content is too low (<1.20%), hardenability is insufficient, making it difficult to obtain a sufficient bainite volume fraction; if the Mn content is too high (>1.80%), it increases the tendency for center segregation in continuously cast billets, worsening weldability and toughness. This invention controls the Mn content to be 1.20%~1.80%, preferably 1.40%~1.65%.
[0024] Mo (Mo): Mo is a core element for improving the high-temperature strength of refractory steel, enhancing its high-temperature stability through solid solution strengthening and delayed carbide coarsening. Traditional refractory steels contain ≥0.40% Mo. This invention, through a multi-element composite microalloying design, significantly reduces the Mo content to 0.10%~0.25%, preferably 0.12%~0.20%, thereby significantly reducing alloy costs while maintaining high-temperature strength. Mo synergistically interacts with Nb, V, and Ti to form composite nano-precipitates such as (Nb,V,Mo)(C,N) and (Ti,Mo)(C,N), improving the thermal stability of the precipitates.
[0025] Niobium (Nb): Nb is a strong carbonitride forming element. During controlled rolling, it achieves fine-grain strengthening by inhibiting austenite recrystallization and grain growth. Simultaneously, during high-temperature service, it precipitates nano-sized NbC or (Nb,Mo)C, providing precipitation strengthening. If the Nb content is too low (<0.020%), the fine-grain strengthening and precipitation strengthening effects are insufficient; if the Nb content is too high (>0.060%), it increases alloy cost and easily forms coarse Nb(C,N) particles, reducing toughness. This invention controls the Nb content to be 0.020%~0.060%, preferably 0.030%~0.050%.
[0026] Vanadium (V): Vanadium has high solid solubility in austenite and precipitates nano-sized vanadium (VC) during or after ferrite / bainite phase transformation, exhibiting a strong secondary hardening effect. Vanadium carbides demonstrate good stability at high temperatures (500℃~700℃) and are a significant contributor to the high-temperature strengthening of refractory steels. Too low a V content (<0.030%) results in insufficient high-temperature precipitation strengthening; too high a V content (>0.080%) increases costs and promotes VC coarsening at high temperatures. This invention controls the V content to be 0.030%~0.080%, preferably 0.040%~0.065%.
[0027] Titanium (Ti): Ti is a strong carbonitride forming element with an extremely strong affinity for nitrogen (N), forming TiN to pin austenite grain boundaries and refine the original austenite grains. More importantly, Ti and Mo can synergistically form a (Ti,Mo)(C,N) composite precipitate, which exhibits an extremely low ripening rate and excellent high-temperature stability. If the Ti content is too low (<0.008%), the grain refinement and composite precipitation effects are insufficient; if the Ti content is too high (>0.025%), liquid-precipitated TiN is easily formed, becoming a crack initiation point and severely deteriorating toughness. This invention controls the Ti content to 0.008%~0.025%, preferably 0.010%~0.020%, and controls the Ti / N ratio to be within the range of 2.5~4.0 to suppress the formation of liquid-precipitated TiN.
[0028] Cr (chromium): Cr can improve the hardenability and oxidation resistance of steel, and works synergistically with Mo to improve high-temperature strength. The Cr content should be controlled between 0.20% and 0.50%, preferably between 0.25% and 0.40%.
[0029] Ni (Ni): Ni can improve the toughness and hardenability of steel, and synergistically improves atmospheric corrosion resistance with Cu. The Ni content should be controlled between 0.10% and 0.30%, preferably between 0.15% and 0.25%.
[0030] Cu (copper): Cu enhances strength through solid solution strengthening and synergistically improves corrosion resistance with Ni. The Cu content is controlled at 0.15%~0.35%, preferably 0.20%~0.30%.
[0031] Als (acid-soluble aluminum): Als is a strong deoxidizing element that can refine grains and form AlN with N to inhibit grain growth. The Als content is controlled at 0.015%~0.050%, preferably 0.020%~0.040%.
[0032] P and S (phosphorus and sulfur): P and S are harmful elements and should be minimized. P segregates at grain boundaries, reducing toughness, while S forms MnS inclusions, deteriorating performance. This invention controls P ≤ 0.020% and S ≤ 0.010%, preferably P ≤ 0.015% and S ≤ 0.008%.
[0033] Nitrogen (N): Nitrogen is a key element in the formation of microalloyed carbonitrides. Appropriate amounts of N can promote the formation of V(C,N), Nb(C,N), and Ti(C,N), improving precipitation strengthening. Too low an N content results in insufficient carbonitride precipitation; too high an N content leads to the formation of coarse TiN or bubble defects. This invention controls the N content to be 0.006%~0.015%, preferably 0.008%~0.012%.
[0034] One of the core innovations of this invention lies in the synergistic design of Mo-Nb-V-Ti quaternary composite microalloying. This invention achieves the following synergistic effects through the optimized proportions of the four elements:
[0035] (1) Formation of composite nanoprecipitates: During the TMCP process and high-temperature service, Nb, V, Ti and Mo synergistically form various MC-type composite carbides such as (Nb,V,Mo)(C,N), (Ti,Mo)(C,N) and (V,Mo)(C,N). Compared with single carbides (such as NbC, TiC, VC), composite carbides have lower aging rates and higher thermal stability, and are less prone to coarsening at high temperatures, thus providing continuous and effective precipitation strengthening.
[0036] (2) Control of small-angle grain boundary density: Through an optimized two-stage controlled rolling process, high-density small-angle grain boundaries (≥3.5 mm / mm²) are formed between bainite laths. These small-angle grain boundaries provide a large number of favorable nucleation sites for MC-type carbides, accelerate the precipitation kinetics at high temperatures, and enable the steel to respond quickly during the fire heating process.
[0037] (3) Temperature compensation mechanism of solid solution-precipitation strengthening: At room temperature, some Nb and Mo are dissolved in the matrix to provide solid solution strengthening; at high temperature, the diffusion of solid solution elements into the matrix and the dynamic precipitation of nano-precipitates compensate for the strength loss caused by the decrease in shear modulus and the failure of fine grain strengthening.
[0038] Another core innovation of this invention lies in the precise control of the ferrite + bainite dual-phase microstructure. By controlling the cooling process, a dual-phase microstructure with a ferrite volume fraction of 35%~65% and a bainite volume fraction of 35%~65% is obtained. Ferrite, as the soft phase, provides good plasticity and a low yield strength ratio (≤0.80), ensuring excellent seismic performance; bainite, as the hard phase, provides high strength and excellent high-temperature microstructure stability. The high-density dislocations and substructures in bainite provide numerous nucleation sites for nanoprecipitates, promoting secondary hardening at high temperatures.
[0039] A method for producing the aforementioned quaternary composite microalloyed steel includes the following steps:
[0040] S100: Smelting and continuous casting: Smelting is carried out in a converter or electric furnace, followed by LF refining and RH vacuum degassing treatment to control the composition of the molten steel to reach the chemical composition range of the quaternary composite microalloyed steel, and then continuously casting into slabs with a thickness of 200mm~300mm.
[0041] S200: Heating: Heat the continuously cast slab to 1180℃~1250℃ for 1.5h~3.0h;
[0042] The heating temperature and time must ensure that microalloying elements such as Nb and V are fully dissolved in austenite, while avoiding excessive austenite grain growth. The preferred heating temperature is 1200℃~1230℃, and the heating time is 2.0h~2.5h.
[0043] S300: Rough rolling: Rough rolling is carried out in the temperature range of 1050℃~1150℃, and the cumulative reduction rate of rough rolling is ≥60% to obtain intermediate billet;
[0044] Austenite recrystallization occurs during rough rolling, refining the austenite grains.
[0045] S400: Finishing rolling: Finishing rolling begins when the intermediate billet temperature drops to 950℃~1050℃, the cumulative reduction rate of finishing rolling is ≥70%, and the final rolling temperature is 780℃~860℃;
[0046] The preferred final rolling temperature is 800℃~840℃. If the final rolling temperature is too low, the rolling load will be too high; if the final rolling temperature is too high, the austenite grains will be coarse and the cooling burden after rolling will be increased.
[0047] S500: Accelerated cooling: After finishing rolling, accelerate cooling at a rate of 15℃ / s to 40℃ / s (preferably 20℃ / s to 35℃ / s) to 580℃ to 680℃ (preferably 620℃ to 660℃).
[0048] Accelerated cooling suppresses high-temperature phase transformation, preserves supercooled austenite, and creates conditions for bainite transformation.
[0049] Air cooling or slow cooling: Slowly cool to a final cooling temperature of 450℃~600℃ at a cooling rate of ≤5℃ / s, preferably 480℃~550℃.
[0050] Slow cooling promotes the precipitation of some ferrite, controls the volume fraction and morphology of bainite, and avoids the formation of martensite.
[0051] The above-mentioned controlled cooling process yields a ferrite + bainite dual-phase microstructure.
[0052] Preferably, in step S400, the finishing rolling adopts a two-stage controlled rolling: the first stage is rolled in the austenite recrystallization zone at 950℃~1050℃, with a cumulative reduction rate ≥40% and a pass reduction rate ≥15%, to promote repeated recrystallization and refinement of austenite; the second stage is rolled at 850℃~950℃, with a cumulative reduction rate ≥30% and a pass reduction rate ≥10%, to accumulate deformation energy and promote ferrite nucleation and bainite transformation.
[0053] Preferably, the production method includes:
[0054] Step S600: Heat treatment: Temper the steel plate at 600℃~650℃ for 15min~120min. Preferably, temper at 620℃~640℃ for 30min~90min. Tempering can further promote the precipitation of nano-sized MC-type composite carbides, improve high-temperature strength stability, eliminate residual stress, and improve toughness.
[0055] The present invention has at least the following beneficial effects:
[0056] (1) Significantly reduce alloy cost: The present invention controls the Mo content at 0.10%~0.25%, which is 40%~75% lower than that of traditional refractory steel (Mo≥0.40%). At the same time, the high temperature strength is compensated by Nb-V-Ti multi-component micro-alloying, and the alloy cost per ton of steel is reduced by 15%~25%.
[0057] (2) Excellent fire resistance: Through the nano-precipitation strengthening mechanism, the yield strength of the steel under the high temperature condition of 600℃×3h is not less than 2 / 3 of the yield strength at room temperature, which meets the technical requirements of fire-resistant steel.
[0058] (3) Good seismic performance: The ferrite + bainite dual-phase microstructure design makes the yield strength ratio ≤0.80, which is lower than the requirement of ≤0.85 for seismic steel, and has excellent plastic deformation capacity and seismic performance.
[0059] (4) Excellent comprehensive mechanical properties: room temperature yield strength ≥460MPa, tensile strength ≥600MPa, elongation after fracture ≥20%, impact energy at -20℃ ≥60J, meeting the requirements of Q460 grade building structural steel.
[0060] (5) Good welding performance: The low carbon design and low Pcm value (≤0.22%) ensure excellent welding performance and are suitable for large-scale welding construction of building steel structures.
[0061] (6) Simple process and strong adaptability: It adopts conventional TMCP process and does not require complex heat treatment. It can be implemented on existing hot rolling or medium and heavy plate production lines. Attached Figure Description
[0062] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0063] Figure 1 The image shows the metallographic microstructure of the steel corresponding to Example 1.
[0064] Figure 2 The image shows the metallographic microstructure of the steel corresponding to Example 2;
[0065] Figure 3 The image shows the metallographic microstructure of the steel corresponding to Example 3;
[0066] Figure 4 This is a 10μm-scale electron microscope image corresponding to Example 1;
[0067] Figure 5 This is a 3μm electron microscope image corresponding to Example 1. Detailed Implementation
[0068] To make the objectives, methods, and advantages of the embodiments of the present invention clearer, the methods in the embodiments of the present invention will be clearly and completely described. Obviously, the described embodiments are some embodiments of the present invention, but not all embodiments.
[0069] Example 1: Experimental steel was smelted according to the composition of the present invention. The chemical composition (mass percentage) was as follows: C: 0.07%, Si: 0.28%, Mn: 1.52%, Mo: 0.15%, Nb: 0.040%, V: 0.050%, Ti: 0.015%, Cr: 0.32%, Ni: 0.20%, Cu: 0.25%, Als: 0.030%, N: 0.010%, with the balance being Fe and unavoidable impurities.
[0070] Unavoidable impurities include: P: 0.012%, S: 0.006%.
[0071] After LF refining and RH vacuum degassing, the composition of the molten steel is controlled to meet the above chemical composition mass percentage, and then continuously cast into slabs;
[0072] The slab was heated to 1220℃ and held for 2.5 hours before rough rolling. The initial rough rolling temperature was 1120℃, and the final rough rolling temperature was 1050℃, with a cumulative reduction of 65% and an intermediate slab thickness of 35mm. Finish rolling employed a two-stage controlled rolling process: the first stage was rolling at 1025℃ with a cumulative reduction of 45%; the second stage was rolling at 910℃ with a cumulative reduction of 35%, and the final rolling temperature was 820℃. After finish rolling, the slab was cooled to 640℃ at an initial cooling rate of 30℃ / s, followed by slow cooling to 520℃ at a rate of 3℃ / s, and finally air-cooled to room temperature. This yielded a hot-rolled steel plate with a thickness of 12mm.
[0073] The hot-rolled steel sheet was tempered at 630℃ for 60 minutes.
[0074] Mechanical property test results:
[0075] Room temperature: Yield strength Rp0.2 = 485 MPa, tensile strength Rm = 655 MPa, elongation after fracture A = 22.5%, yield strength ratio = 0.74;
[0076] High-temperature tensile test at 600℃ for 3 hours: Yield strength = 335 MPa, which is 69.1% of the room temperature yield strength;
[0077] Impact energy at -20℃ KV2=78J;
[0078] The welding crack susceptibility index Pcm = 0.198%.
[0079] Metallographic microstructure photographs such as Figure 1 As shown, the microstructure analysis shows that the volume fraction of ferrite is 45%, the volume fraction of bainite is 55%, and the size of the bainite lath bundles is 12 μm.
[0080] TEM observation showed that the average size of the nano-sized MC-type composite carbide in the rough rolling state was 8 nm, with a mass fraction of 0.032%; after tempering at 630℃ for 60 min, the average size was 10 nm, with a mass fraction of 0.058%, of which particles with a size <10 nm accounted for 62%.
[0081] Example 2: Experimental steel was smelted according to the composition of the present invention. The chemical composition (mass percentage) was as follows: C: 0.12%, Si: 0.45%, Mn: 1.80%, Mo: 0.25%, Nb: 0.060%, V: 0.080%, Ti: 0.025%, Cr: 0.50%, Ni: 0.30%, Cu: 0.35%, Als: 0.050%, N: 0.015%, with the balance being Fe and unavoidable impurities.
[0082] Unavoidable impurities include: P: 0.010%, S: 0.005%.
[0083] After LF refining and RH vacuum degassing, the composition of the molten steel is controlled to meet the above chemical composition mass percentage, and then continuously cast into slabs;
[0084] The slab was heated to 1250℃ and held for 3.0 hours before rough rolling. The initial rough rolling temperature was 1150℃, and the final rough rolling temperature was 1060℃, with a cumulative reduction of 62% and an intermediate slab thickness of 38mm. Finish rolling employed a two-stage controlled rolling process: the first stage was rolling at 1050℃ with a cumulative reduction of 42%; the second stage was rolling at 950℃ with a cumulative reduction of 38%, and the final rolling temperature was 840℃. After finish rolling, the slab was cooled to 680℃ at an initial cooling rate of 40℃ / s, followed by slow cooling to 600℃ at 4℃ / s, and finally air-cooled to room temperature. A hot-rolled steel plate with a thickness of 16mm was obtained.
[0085] The hot-rolled steel sheet was tempered at 650℃ for 120 minutes.
[0086] Mechanical property test results:
[0087] Room temperature: Yield strength Rp0.2 = 520 MPa, tensile strength Rm = 705 MPa, elongation after fracture A = 20.8%, yield strength ratio = 0.74;
[0088] High-temperature tensile test at 600℃ for 3 hours: Yield strength = 365 MPa, which is 70.2% of the room temperature yield strength;
[0089] Impact energy at -20℃: KV2=72J;
[0090] The welding crack susceptibility index Pcm = 0.215%.
[0091] Metallographic microstructure photographs such as Figure 2 As shown, the microstructure analysis shows that the volume fraction of ferrite is 40%, the volume fraction of bainite is 60%, and the size of the bainite lath bundles is 10 μm.
[0092] TEM observation showed that the average size of the nano-sized MC-type composite carbide in the rough rolling state was 7 nm with a mass fraction of 0.038%; after tempering at 650℃ for 120 min, the average size was 9 nm with a mass fraction of 0.065%, of which particles with a size <10 nm accounted for 58%.
[0093] Example 3: Experimental steel was smelted according to the composition of the present invention. The chemical composition (mass percentage) was as follows: C: 0.05%, Si: 0.15%, Mn: 1.20%, Mo: 0.10%, Nb: 0.020%, V: 0.030%, Ti: 0.008%, Cr: 0.20%, Ni: 0.10%, Cu: 0.15%, Als: 0.015%, N: 0.006%, with the balance being Fe and unavoidable impurities.
[0094] Unavoidable impurities include: P: 0.014%, S: 0.007%.
[0095] After LF refining and RH vacuum degassing, the composition of the molten steel is controlled to meet the above chemical composition mass percentage, and then continuously cast into slabs;
[0096] The slab was heated to 1180℃ and held for 1.5 hours before rough rolling. The initial rough rolling temperature was 1050℃, and the final rough rolling temperature was 1040℃, with a cumulative reduction of 68% and an intermediate slab thickness of 32mm. Finish rolling employed a two-stage controlled rolling process: the first stage was rolling at 950℃ with a cumulative reduction of 48%; the second stage was rolling at 850℃ with a cumulative reduction of 32%, and the final rolling temperature was 800℃. After finish rolling, the slab was cooled to 580℃ at an initial cooling rate of 15℃ / s, followed by slow cooling to 450℃ at a rate of 2℃ / s, and finally air-cooled to room temperature. This yielded a hot-rolled steel plate with a thickness of 10mm.
[0097] The hot-rolled steel sheet was tempered at 600℃ for 15 minutes.
[0098] Mechanical property test results:
[0099] Room temperature: Yield strength Rp0.2 = 465 MPa, tensile strength Rm = 625 MPa, elongation after fracture A = 24.0%, yield strength ratio = 0.74;
[0100] High-temperature tensile test at 600℃ for 3 hours: Yield strength = 318 MPa, which is 68.4% of the room temperature yield strength;
[0101] Impact energy at -20℃ KV2=85J;
[0102] The welding crack susceptibility index Pcm = 0.185%.
[0103] Metallographic microstructure photographs such as Figure 3 As shown, the microstructure analysis shows that the volume fraction of ferrite is 55%, the volume fraction of bainite is 45%, and the size of the bainite lath bundles is 14 μm.
[0104] TEM observation showed that the average size of the nano-sized MC-type composite carbide in the rough rolling state was 9 nm with a mass fraction of 0.025%; after tempering at 620℃ for 90 min, the average size was 11 nm with a mass fraction of 0.048%, of which particles with a size <10 nm accounted for 55%.
[0105] Comparative Example 1 (High Mo conventional refractory steel): Chemical composition (mass percentage) is: C: 0.08%, Si: 0.30%, Mn: 1.50%, Mo: 0.50%, Nb: 0.020%, V: 0.020%, Ti: 0.005%, Cr: 0.30%, Ni: 0.15%, Cu: 0.20%, Als: 0.025%, P: 0.012%, S: 0.006%, N: 0.008%, balance Fe.
[0106] The same rolling and cooling process as in Example 1 was used.
[0107] Mechanical property test results:
[0108] Room temperature: Yield strength Rp0.2 = 495 MPa, tensile strength Rm = 670 MPa, elongation after fracture A = 21.0%, yield strength ratio = 0.74;
[0109] High-temperature tensile test at 600℃ for 3 hours: Yield strength = 342 MPa, which is 69.1% of the room temperature yield strength;
[0110] Impact energy at -20℃ KV2=65J;
[0111] The welding crack susceptibility index Pcm = 0.258%.
[0112] Compared with Example 1, Comparative Example 1 has a Mo content of 0.50%, which significantly increases the alloy cost, but its refractory performance is comparable to that of Example 1; and its Pcm value is higher, resulting in poorer weldability.
[0113] Comparative Example 2 (low-Mo steel with increased Nb content): Chemical composition (mass percentage) is as follows: C: 0.07%, Si: 0.28%, Mn: 1.52%, Mo: 0.15%, Nb: 0.080%, V: 0.005%, Ti: 0.005%, Cr: 0.32%, Ni: 0.20%, Cu: 0.25%, Als: 0.030%, P: 0.012%, S: 0.006%, N: 0.010%, balance Fe.
[0114] The same rolling and cooling process as in Example 1 was used.
[0115] Mechanical property test results:
[0116] Room temperature: Yield strength Rp0.2 = 475 MPa, tensile strength Rm = 640 MPa, elongation after fracture A = 20.5%, yield strength ratio = 0.74;
[0117] High-temperature tensile test at 600℃ for 3 hours: Yield strength = 278 MPa, which is 58.5% of the room temperature yield strength (not meeting the ≥2 / 3 requirement).
[0118] Impact energy at -20℃: KV2=55J.
[0119] Compared with Example 1, Comparative Example 2 has a higher Nb content (0.080%), but the V and Ti contents are too low, lacking the synergistic effect of multi-component composite microalloying. The number of nano-precipitates at high temperature is insufficient, and the refractory performance does not meet the standard.
[0120] Comparative Example 3 (increased V and Ti content, low Mo steel, low Nb steel): Chemical composition (mass percentage) is: C: 0.07%, Si: 0.28%, Mn: 1.52%, Mo: 0.15%, Nb: 0.015%, V: 0.07%, Ti: 0.024%, Cr: 0.32%, Ni: 0.20%, Cu: 0.25%, Als: 0.030%, P: 0.012%, S: 0.006%, N: 0.010%, balance Fe.
[0121] The same rolling and cooling process as in Example 1 was used.
[0122] Mechanical property test results:
[0123] Room temperature: Yield strength Rp0.2 = 525 MPa, tensile strength Rm = 640 MPa, elongation after fracture A = 16.5%, yield strength ratio = 0.82;
[0124] High-temperature tensile test at 600℃ for 3 hours: Yield strength = 315 MPa, which is 60.0% of the room temperature yield strength (not meeting the ≥2 / 3 requirement).
[0125] Impact energy at -20℃: KV2 = 50J.
[0126] Compared with Example 1, Comparative Example 3 uses the traditional method of increasing the vanadium and titanium content in steel to improve the performance of microalloyed steel. However, the Mo and Nb contents are too low, lacking the synergistic effect of multi-component composite microalloying, resulting in insufficient toughness of the steel and failing to meet the yield strength ratio requirements.
[0127] Comparative Example 4 (high bainitic single-phase steel): The chemical composition is the same as that of Example 1, but a direct quenching process is used: after finishing rolling, the steel is cooled to 300°C at a front cooling rate of 50°C / s to obtain an almost all-bainitic structure (bainite volume fraction >90%).
[0128] Mechanical property test results:
[0129] Room temperature: Yield strength Rp0.2 = 565 MPa, tensile strength Rm = 720 MPa, elongation after fracture A = 16.0%, yield strength ratio = 0.78;
[0130] High-temperature tensile test at 600℃ for 3 hours: Yield strength = 385 MPa, which is 68.1% of the room temperature yield strength;
[0131] Impact energy at -20℃: KV2=45J.
[0132] Compared with Example 1, Comparative Example 3, although its high-temperature strength meets the standard, has a high yield strength ratio of 0.78, which is close to the upper limit. Its elongation after fracture and impact energy are significantly reduced, and its ductility, toughness and seismic performance are insufficient.
[0133] Table 1 summarizes the main performance comparisons of the embodiments and comparative examples.
[0134] Table 1. Performance Comparison of Examples and Comparative Examples
[0135] project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 C / % 0.07 0.09 0.06 0.08 0.07 0.07 0.07 Mo / % 0.15 0.18 0.12 0.5 0.15 0.15 0.15 Nb / % 0.04 0.05 0.03 0.02 0.08 0.015 0.04 V / % 0.05 0.06 0.04 0.02 0.005 0.07 0.05 Ti / % 0.015 0.018 0.012 0.005 0.005 0.024 0.015 Ferrite / % 45 40 55 42 48 20 <10 Bainite / % 55 60 45 58 52 80 >90 Rp0.2 / MPa 485 520 465 495 475 525 565 Rm / MPa 655 705 625 670 640 640 720 A / % 22.5 20.8 24 21 20.5 16.5 16 The ratio of yield strength 0.74 0.74 0.74 0.74 0.74 0.82 0.78 Yield strength at 600℃ / MPa 335 365 318 342 278 315 385 Yield strength ratio at 600℃ / room temperature 0.691 0.702 0.684 0.691 0.585 0.600 0.681 -20℃KV2 / J 78 72 85 65 55 50 45 Pcm / % 0.198 0.215 0.185 0.258 0.202 0.199 0.198
[0136] As can be seen from Table 1, Examples 1 to 3 of the present invention all meet the technical indicators of refractory steel, namely, yield strength at 600℃ ≥ 2 / 3 of room temperature yield strength, and have excellent room temperature mechanical properties, good plasticity and toughness and low yield strength ratio.
[0137] Compared with Comparative Example 1 (high-Mo conventional refractory steel), the present invention reduces the Mo content by 40%~75% while maintaining the same refractory performance, significantly reducing the alloy cost, while significantly improving the weldability, with Pcm≤0.22%.
[0138] Compared with Comparative Example 2 (low Mo steel with increased Nb content), this invention, through Mo-Nb-V-Ti multi-element composite design, fully leverages the synergistic effect of each element, resulting in a significantly better high-temperature precipitation strengthening effect than single microalloying.
[0139] Compared with Comparative Example 3 (increased V and Ti content, low Mo steel, low Nb steel), the present invention provides a synergistic effect of increasing Mo and Nb content to achieve multi-component composite microalloying, while ensuring the toughness of the steel and reducing the V and Ti content.
[0140] Compared with Comparative Example 4 (high bainitic single-phase structure), the ferrite + bainitic dual-phase structure design of the present invention significantly improves ductility, toughness and seismic performance while ensuring fire resistance.
[0141] Figure 4 and Figure 5The image shown is an electron microscope image of the steel corresponding to Example 1. The precipitated phases in the steel were observed using a transmission electron microscope. Selected area electron diffraction (SED) analysis determined it to be a face-centered cubic (MC) type structure.
[0142] Energy dispersive spectroscopy (EDS) confirmed that the particles contain Nb, V, Mo, C, N (and Ti, Mo, C, N).
[0143] The equivalent circle diameter of the particles was measured using ImageJ software on TEM bright-field images. The MC-type composite carbide particles have a size distribution range of 3 nm to 18 nm, with a peak value between 7 nm and 9 nm. Nanoscale MC-type composite carbide precipitates are distributed in steel. The main types of MC-type composite carbides include (Nb,V,Mo)(C,N) and (Ti,Mo)(C,N), with a size distribution range of 3 nm to 18 nm.
[0144] In summary, this invention has successfully developed a low-cost fire-resistant building steel with excellent fire resistance, good seismic performance, and superior comprehensive mechanical properties through low-carbon, low-molybdenum, multi-component composite microalloying composition design and optimized TMCP process. It can be widely used in important building structures with high requirements for fire resistance and seismic performance, such as high-rise steel structure buildings, large-span public buildings, stadiums, and airport terminals.
[0145] The above are merely preferred embodiments of the present invention and are not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A quaternary composite microalloyed steel, characterized in that, The chemical composition, by weight percentage, includes: C: 0.05%~0.12%, Si: 0.15%~0.45%, Mn: 1.20%~1.80%, Mo: 0.10%~0.25%, Nb: 0.020%~0.060%, V: 0.030%~0.080%, Ti: 0.008%~0.025%, Cr: 0.20%~0.50%, Ni: 0.10%~0.30%, Cu: 0.15%~0.35%, Als: 0.015%~0.050%, N: 0.006%~0.015%, with the balance being Fe and unavoidable impurities; Unavoidable impurities include P and S, with P ≤ 0.020% and S ≤ 0.010%.
2. The quaternary composite microalloyed steel according to claim 1, characterized in that, The microstructure of steel consists of ferrite and bainite, with ferrite having a volume fraction of 45% to 55% and bainite having a volume fraction of 45% to 60%.
3. The quaternary composite microalloyed steel according to claim 2, characterized in that, The bainite is lath bainite, and the size of the bainite lath bundles is ≤15μm.
4. The quaternary composite microalloyed steel according to claim 1, characterized in that, The steel contains nanoscale MC-type composite carbide precipitates, the main types of which include (Nb,V,Mo)(C,N) and (Ti,Mo)(C,N), and the size distribution range of the nanoscale MC-type composite carbide is 3nm~18nm.
5. The quaternary composite microalloyed steel according to claim 4, characterized in that, The mass fraction of the nanoscale MC-type composite carbide in the rough rolling state is 0.025%~0.038%, and the mass fraction after high-temperature tempering is 0.048%~0.065%, wherein the nanoscale MC-type composite carbide with a size of less than 10nm accounts for no less than 55% of the total mass fraction of the MC-type composite carbide.
6. The quaternary composite microalloyed steel according to claim 1, characterized in that, The small-angle grain boundary density of steel is ≥3.5mm / mm².
7. The quaternary composite microalloyed steel according to any one of claims 1-6, characterized in that, Yield strength at room temperature ≥460MPa, tensile strength ≥600MPa, elongation after fracture A ≥20%, yield strength ratio ≤0.80; The yield strength under high-temperature tensile conditions of 600℃×3h is not less than 2 / 3 of the yield strength at room temperature.
8. A method for producing the quaternary composite microalloyed steel according to any one of claims 1-7, characterized in that, Includes the following steps: S100: Smelting and continuous casting: After LF refining and RH vacuum degassing, the composition of the molten steel is controlled to reach the chemical composition range of the quaternary composite microalloyed steel described in claim 1, and then continuously cast into slabs; S200: Heating: Heat the continuously cast slab to 1180℃~1250℃ for 1.5h~3.0h; S300: Rough rolling: Rough rolling is carried out in the temperature range of 1050℃~1150℃, and the cumulative reduction rate of rough rolling is ≥60% to obtain intermediate billet; S400: Finishing rolling: Finishing rolling begins when the intermediate billet temperature drops to 950℃~1050℃, the cumulative reduction rate of finishing rolling is ≥70%, and the final rolling temperature is 780℃~860℃; S500: Cooling: After finishing rolling, accelerated cooling is carried out at a cooling rate of 15℃ / s~40℃ / s. After cooling to 580℃~680℃, air cooling or slow cooling is carried out to obtain steel. The final cooling temperature is 450℃~600℃; the air cooling or slow cooling rate is ≤5℃ / s.
9. The production method according to claim 8, characterized in that, In step S400, the finishing rolling adopts a two-stage controlled rolling process: the first stage is rolled at 950℃~1050℃ with a cumulative reduction rate ≥40%; the second stage is rolled at 850℃~950℃ with a cumulative reduction rate ≥30%.
10. The production method according to claim 8 or 9, characterized in that, include: Step S600: Heat treatment: The steel plate is tempered at 600℃~650℃ for 15min~120min.
Citation Information
Patent Citations
Heat-resistant steel product and method for production thereof
CN101171354B
A low-carbon bainitic structural steel with a yield strength ratio <0.8 and its production method
CN103667963B
